2012
DOI: 10.20533/licej.2040.2589.2012.0079
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender and Family Background on the Effectiveness of Client Centered and Rational Emotive Behaviour Counselling Therapies in Enhancing the SelfConcept of Adolescents

Abstract: Among the Counselling approaches adopted to assist adolescents to solve their problems are the Client-Centered Therapy (CCT) and the Rational Emotive Bahaviour Therapy (REBT). Counsellors in Nigeria adopt any of the two approaches whenever a client presents a problem, without regard to the relative effectiveness of the approaches. The client-centered therapy belongs to the existential humanistic school of thought while the rational emotive behaviour therapy belongs to the cognitive behaviour school. The two th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Future studies should include the demographic variables in the analysis to find out if there will be an interaction effect between demographic variables and REHT intervention for HIV-positive patients who indulge in alcohol drinking. Previous studies [18,3133] have indicated that REBT programs are not usually disrupted by small sample sizes. This information notwithstanding, upcoming researchers should endeavor to use larger sample sizes to study the effectiveness of REHT on HIV-positive persons in the Nigerian communities.…”
Section: Limitations and Suggestions For Further Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should include the demographic variables in the analysis to find out if there will be an interaction effect between demographic variables and REHT intervention for HIV-positive patients who indulge in alcohol drinking. Previous studies [18,3133] have indicated that REBT programs are not usually disrupted by small sample sizes. This information notwithstanding, upcoming researchers should endeavor to use larger sample sizes to study the effectiveness of REHT on HIV-positive persons in the Nigerian communities.…”
Section: Limitations and Suggestions For Further Studiesmentioning
confidence: 99%
“…For instance, studies indicate that therapists’ sex could account for variability in treatment outcome. [3133] There also are other variables between patients and therapists that could affect therapeutic alliance, outcomes, and engagement. For instance, active, engaging, and extraverted therapists may generate faster symptom reduction in short-term therapy, whereas nonintrusive therapists may produce better outcome in long-term therapy.…”
Section: Limitations and Suggestions For Further Studiesmentioning
confidence: 99%
“…[ 58 , 59 ] Also, the effectiveness of rational emotive behavioral therapy was justified in assisting students to cushion the effect of their academic problems, and personal and social life. [ 60 ] Owuamanam, Ajidahun, and Owuamanam [ 61 ] revealed that REBT is effective in enhancing the self-concept of adolescents. Thus, the finding of this study is a very interesting technique to help adolescents improve greatly and adjust properly in and outside school environs.…”
Section: Discussionmentioning
confidence: 99%